2015
DOI: 10.1039/c5ra07821k
|View full text |Cite
|
Sign up to set email alerts
|

Alginate fibers embedded with silver nanoparticles as efficient catalysts for reduction of 4-nitrophenol

Abstract: Silver nanoparticles (AgNPs) have attracted much attention as promising catalysts in various electron transfer reactions due to their high catalytic efficiency. However, their poor stability results in the decrease of the catalytic efficiency and the poor cycling performance, which have hindered the practical application of AgNPs. In this work, alginate fibers embedded with AgNPs were prepared via in situ reduction of Ag + -alginate fibers in the presence of glucose. Field emission scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…More oxygen adsorbed on the Ce 2 O 3 doped NCs sensor surface, more oxidizing potentiality, and faster oxidation of 2-NP can be occurred. The action of 2-NP can be extremely immense as compare to other toxic chemicals with the surface under identical conditions [47, 48]. 2-NP can be converted into cyclohexa-3, 5-diene-1, 2-dione under reduction and subsequently oxidation onto the surface of Ce 2 O 3 .CNT NCs whether in exterior or interior of particle-surface or interior-tube.…”
Section: Applicationsmentioning
confidence: 99%
“…More oxygen adsorbed on the Ce 2 O 3 doped NCs sensor surface, more oxidizing potentiality, and faster oxidation of 2-NP can be occurred. The action of 2-NP can be extremely immense as compare to other toxic chemicals with the surface under identical conditions [47, 48]. 2-NP can be converted into cyclohexa-3, 5-diene-1, 2-dione under reduction and subsequently oxidation onto the surface of Ce 2 O 3 .CNT NCs whether in exterior or interior of particle-surface or interior-tube.…”
Section: Applicationsmentioning
confidence: 99%
“…prepared alginate/poly(caprolactone) composite nanofibros scaffolds using a dual‐jet co‐eletrospinning system, and found that both chemical properties and hydrophobicity of scaffolds were manipulated by regulating the perfusion rates of polymer jets. In addition, functional nanoparticles such as silver nanoparticle and ferric oxide nanoparticle were introduced into SA fiber to render the fiber with special properties …”
Section: Introductionmentioning
confidence: 99%
“…Some of the main benefits of fibrous catalysts include the flexibility of form, low resistance to flow of gas and liquids through a bundle of fibers, high permeability due to their large specific surface area, safer operations, easy scale up, and reusability . In recent years, much effort has been focused on the development of effective strategies to incorporate Ag NPs within various fibers, such as natural fibers like collagen fibers and cellulose fibers and synthesized fibers such as carbon nanofibers, POM/PLLA electro‐spun fibers, alginate fibers, and PAN fibers . For the purpose of full exposure of catalytic Ag NPs, substantial effort has been directed towards uniform surface‐localized particles with various synthesized fibers with functional groups allowing effective chemical or physical interactions with the metal ions or formed NPs .…”
Section: Introductionmentioning
confidence: 99%